World reimagined: Americans and human rights in the twentieth century - Bradley, Mark (UK, Cambridge, 2016)
"For readers who want to understand why human rights has become the moral language of our time. It explores the making of a twentieth century global human rights imagination and its American vernaculars in times of war, decolonization and globalization during the transformative decades of the 1940s and 1970s"--Provided by publisher.
Introduction: How it feels to be free -- Part One. The 1940s -- At home in the world -- The wartime rights imagination -- Beyond belief -- Conditions of possibility -- Part Two. The 1970s -- Circulations -- American vernaculars I -- American vernaculars II -- The movement -- Coda: The sense of an ending.
Includes bibliographical references and index.
Keywords: Human rights -- United States; Human rights; Social change; War; Decolonization; Globalization; Transnationalism; World politics